PERAN MAKNA DALAM PENERJEMAHAN - Rosyidi, Abdul Wahab (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2007)
Basically translating is not merely transferring meaning behind the words or sentences in a source language into a target language, but also considering many things to identify the real meaning such as, situational, linguistic, and cultural contexts.We should take into account some principles regarding the word meaning, that is, 1) meaning is changeable due to the time change, and the change is not an absolute requirement for any word; 2) a word in a language with different dialects may have different meanings, it is due to the meaning extension and reduction; 3) a word does not refer toÂ  the thing it refers to, but it is only a symbol; and 4) a word often has more than one meaning. Therefore, meaning has an important role in a process of translation from a source language into the a target language. For that reason, a translator has to consider which component of meaning accuracy is in line with the meaning in the source language to be translated into the target language.